Assessing the Temperamental Basis of the Sense of Humor: Adaptation of the English Language Version of the State-Trait Cheerfulness Inventory Long and Standard Form - Hofmann, Jennifer; Carretero-Dios, Hugo; Carrell, Amy (Frontiers in Psychology, 2018)
The State-Trait Model of Cheerfulness assesses the temperamental basis of the sense of humor with the traits and respective states of cheerfulness, seriousness, and bad mood. While trait cheerfulness accounts for 90% of the variance in frequently used sense of humor questionnaires and explains both, the disposition to engaging in smiling and laughter, as well as humor behaviors, trait seriousness and bad mood are antagonistic to the elicitation of amusement (albeit for different reasons). Several studies have shown the validity and reliability of the STCI questionnaire in German and other language versions (i.e., Spanish). In this study, the English language version with 106 items (STCI-T<106>) was translated, checked for its item and scale characteristics, and tested with a confirmatory factor analysis approach (N = 1101) to investigate the factorial validity of the STCI-T<106> scale. Results show good psychometric characteristics, good internal consistencies, and a fit to the postulated underlying structure of the STCI-T. Then, the standard form with 60 items (STCI-T<60>) was developed and the psychometric characteristics initially tested. In an independent sample (N = 169), the characteristics of the standard form were compared to the parent form and German equivalent. It showed good psychometric characteristics, internal consistencies, as well as a good self- and peer-report congruence. To conclude, the STCI-T<106> is the measure of choice for the assessment of the temperamental basis of the sense of humor and the separate facets of the traits, while the standard form (60 items) allows of an economic assessment of cheerfulness, seriousness, and bad mood, free of context-saturated items and humor preferences.